Slang Lost in Translation? : Prison Slang in Wentworth and Its Translations into Finnish in Subtitling - Rantala, Sarina (My University, 2025)
This master’s thesis studies the slang terms and their Finnish translations in the subtitles of an Australian TV series Wentworth. The aim and purpose of the study are to find out what kind of subtitling strategies the translators have used when translating the slang language to Finnish, and to what extent the translator has considered the intended meaning of the slang expressions and transferred the intended meaning to Finnish. The series takes place in a women’s correctional centre, and the study focuses on slang terms that can be defined as criminal- and prison-related language. A total of nineteen prison-related terms were found in ten episodes of Wentworth season one. The research material was analysed following the subtitling strategies for culture-bound vocabulary, functionality levels of audiovisual translation, and the Quality Recommendations for Finnish Subtitling. The constraints of audiovisual translating were discussed in the analysis when they seemed relevant as well. The slang terms in the series were found to represent six of the presented subtitling strategies. In the analysis, the slang terms were categorised according to the distinctive characteristics of the subtitling strategies, and the characteristics were discussed by comparing the original slang term to the translation considering meaning and possible connotations. Some terms had characteristics of multiple strategy categories, while some recurring terms were translated differently between episodes and could therefore be placed in multiple strategy categories. Possible reasoning behind the translation choices was considered and discussed through the functionality levels and quality recommendations. It was found that of these strategies, transferring the source language term into “a familiar concept in the target language” and generalising or specifying the slang terms were the most frequently utilised strategies for translating the slang vocabulary. It can be said that in audiovisual translating, like other types of translating, keeping the specific vocabulary similar to the source language can be considered as a goal, as it helps to maintain the characteristics of the programme in the target language.
Keywords: slang, audiovisual translation, subtitles, subtitling strategies, functionality levels